Freshwater and Land Mollusk Diversity Patterns Along Dakil River at the University of the Philippines Laguna Land Grant (UPLLG), Paete, Laguna, Luzon Island, Philippines - Perez, Kinsley Meg G.; Parcon, Julius A.; de Chavez, Emmanuel Ryan C. (Science Diliman: A Journal of Pure and Applied Sciences, 2022)
Prior to this study, there had been no malacofaunal study in the University of the Philippines Laguna Land Grant (UPLLG). To address this, a diversity survey of its freshwater and land mollusks was conducted. A total of 25 quadrats (15 m2) on upstream and downstream stations along Dakil River and its tributaries for freshwater mollusks and 12 quadrats (100 m2) for land snails were set randomly to correlate their diversity patterns with environmental variables. From 115 individuals of freshwater mollusks, seven species (six gastropods, one bivalve) belonging to six families (Ampullariidae, Corbiculidae, Lymnaeidae, Neritinidae, Thiaridae, and Viviparidae) were identified. On the other hand, seven species belonging to three families (Ariophantidae, Camaenidae, and Chronidae) were identified among 28 land snail individuals. Malacofaunal survey revealed that the area along Dakil River has low diversity in both freshwater mollusk (H’=1.40) and land snail (H’=1.19). Generalized linear mixed models (GLMM) revealed river velocity was the most significant predictor for species richness of freshwater mollusks, and abundance was highly affected by temperature and inversely affected by canopy cover. Furthermore, altitude was the most significant predictor for species richness of land snails and canopy cover for abundance. Understanding the molluscan diversity could help determine the environment and ecological conditions of the watershed for its effective management and conservation.
Keywords: Diversity, freshwater mollusks, land snails, Dakil River, species richness, abundance